Nance-Horan syndrome, congenital cataracts and dental anomalies - Ana Maria Rodriguez Diaz; Aida Perez Alfonso; Noel Taboada Lugo; Barbara Toledo Pimentel (Editorial Ciencias Médicas, 2020)
Introduction: The presence of atypical dentofacial structures may be the first indicator of other congenital defects related to syndromes of likewise genetic origin. Nance-Horan syndrome is a monogenic X linked disorder phenotypically characterized by distinctive dysmorphic dental and craniofacial alterations, congenital cataracts and cognitive deficit. Objective: Describe an unusual case of dental anomalies in the course of Nance-Horan syndrome. Case presentation: A case is presented of a white male 13-year-old patient. Clinical examination revealed a dysmorphic pattern characterized by long narrow facies, prominent ears with auricular anteversion, a big nose with a high nasal bridge, generalized diastema in both arches, and all the teeth microdontic and abnormally shaped. Periapical radiological examination found short roots and broad pulp chambers. The personal pathological antecedents of the patient, the dysmorphic craniofacial pattern and the radiographs correspond to characteristics of other cases of Nance-Horan syndrome reported in the literature. Mutation of the Nance-Horan syndrome gene is completely expressed only in males. Since males are hemizygous for X linked genes, one copy of the mutated allele is sufficient for the appearance of a sex-linked recessive inheritance disease. Conclusions: Evidence was found of the crucial importance of conducting careful examination, both clinical and radiographic, of patients with dental anomalies. Emphasis is placed on the joint work of various disciplines and specialties, both medical and dental.